Perilaku Merokok pada Remaja dan Faktor Penyebabnya di SMA 2 dan SMK 8 Muhammadiyah Tanjung Sari Kecamatan Medan Selayang : The Smoking Behavior of Adolescents and its Causal Factors in SMA 2 and SMK 8 Muhammadiyah Tanjung Sari, Medan Selayang Sub-district - solihin, Solihin; Nyorong, Mappeaty; Nur’aini, Nur’aini; Siregar, Dian Maya Sari (Poltekes Kemenkes Tanjungpinang, 2023)
One of the health problems that is still a national problem is the large population and high prevalence of smoking. Smoking behavior is difficult to avoid in adolescents due to several factors such as behavior and the environment around adolescents. The objective of the study was to determine the relationship of smoking behavior among adolescents in SMA 2 and SMK 8 Muhammadiyah Tanjung Sari, Medan Selayang Sub-district.The study used quantitative methods through an analytic survey with a Cross-Sectional Study approach. The population in this study was all male students. The sample used a purposive sampling technique for as many as 85 students. Data were analyzed using univariate and bivariate analysis. There was a relationship between knowledge, trust, exposure to cigarette advertising, availability of cigarettes, the role of parents, the role of teachers, and the role of peers on smoking behavior in adolescents at the research site. The most dominant factor was knowledge. The conclusion of this study was all variables have a relationship to smoking behavior in adolescents at SMA 2 and SMK 8 Muhammadiyah Tanjung Sari, Medan Selayang Subdistrict. It is recommended that schools overcome smoking among adolescents through counseling activities about the dangers of smoking, implementing Smokefree Areas (KTR), and conducting routine raids for smokers throughout the school environment.